Productivity and Total Quality Management: Application in Maine Manufacturing - Joseph, John (Maine Policy Review, 1994)
Total quality management [TQM] is among the best known of the new management practice theories that are being tried in and adapted to business organizations. John M. Joseph, Jr. examines the implications of TQM approaches for Maine manufacturers. Joseph's research, which analyzed several TQM surveys, including one he conducted with associates at Thomas College, suggests that although quality management initiatives are not easy to undertake, they are worthwhile.
Keywords: Total quality management; TQM; Maine